Business Strategy: Case Study of Umi, Lahadeng Corner, and Nuca MSMEs - Mustika, Nilam Sari; Hermawan, Agus; Siswanto, Ely (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to know the right business strategy for Umi, Lahadeng Corner, and Nuca MSMEs. The research method uses a multi-sites case study. Also use Strength, Weakness, Opportunity, Threat (SWOT) analysis and Quantitative Strategic Planning Matrix (QSPM) analysis. The results of using SWOT analysis show that the position of each MSME is in quadrant I, which is the most profitable situation. The right strategy in this situation is to implement policies to support and focus on aggressive growth. The results of using QSPM analysis show that an alternative strategy that Umi MSME can prioritize is collaborating with more resellers. The alternative strategy priority for Lahadeng Corner and Nuca MSME is optimizing production capacity. The last strategy alternative for Lahadeng Corner is add production equipment with maximum function. And the last strategy alternative for Umi and Nuca MSMEs is to carry out promotions. The use of SWOT and QSPM analysis in multi-sites case study and comparative research is novelty in this study. Based on the result of the SWOT and QSPM analysis, contribution of the research is can help the owners of Umi, Lahadeng Corner, and Nuca MSMEs in adopting business strategies that suit their companies.